FASHION DESIGN LOOKBOOK PROMOTION NANA RF SHOP - YOLA TRY INDRA, Ir. Drs. Heldi, M.Si., Ph,.D. Dra. Zubaidah, M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
Nana Rf Shop is a women's clothing store that is devoted to adult teens. Nana Rf Shop is categorized as a women's clothing store that provides a variety of simple casual clothes. At present promotions are carried out only through social media such as Instagram and result in a lack of promotion for new product introductions to consumers. The purpose of Nana Rf Shop loobook fashion design in the form of print media is to provide information and visualization directly about Nana Rf Shop products that are designed in an informative and communicative manner so that the information conveyed can be easily understood easily in order to inspire customers to mix and match fashion and add value to satisfaction customers besides promotion. The method used is a SWOT analysis of strengths, weaknesses, opportunities, and threats. To meet the problem at hand. The design process starts from documentation, print media, observation, and interviews with the owner of Nana Rf Shop to find out the development of Nana Rf Shop's fashion business that needs to be improved in terms of promotion. Supporting media used to support the main media of this lookbook include member cards, posters, paper bags, hang tags, stickers, key chains.Keywords: Promotion, Lookbook, Fashion